Correction: Research progress in architecture and application of RRAM with computing-in-memory. Issue 7 (20th March 2023) - Wang, Chenyu; Shi, Ge; Qiao, Fei; Lin, Rubin; Wu, Shien; Hu, Zenan
Abstract : Correction for 'Research progress in architecture and application of RRAM with computing-in-memory' by Chenyu Wang et al., Nanoscale Adv., 2023, ; https://doi.org/10.1039/d3na00025g .